Cesário Verde’s prosaic poetry - Daud, Roberto (ITINERÁRIOS – Revue de Littérature, 2008)
This essay is about the book O Livro de Cesário Verde (1887). A comparison is made between the author, Cesário Verde (1855-1886), and the most important novelist of his time, Eça de Queirós. Based on these comparisons, we want to demonstrate the specificity of the work of Cesário Verde in relation to the period in which he wrote, pointing out the relationship between the writer’s poetry and some aspects of the nineteenth century prose. The research also tries to determine his importance in the formation of the Modern Portuguese poetry.